Disseminated intracranial xanthoma disseminatum: a rare case report and review of literature - Yang, Guang-Zhi (Diagn Pathol, 2016)
BACKGROUND: Xanthoma disseminatum (XD) is a rare benign histiocytic proliferating disease of non-Langerhans cell origin, which is clinically mainly characterized by cutaneous or mucous lesions. Although XD is acknowledged of one systematic disease, involvement of the central nervous system is quite rare. CASE PRESENTATION: We presented one 34-year-old Chinese female with disseminated intracranial XD without cutaneous or oral mucosal papules and masses of the other organs. MR imaging displayed multiple heterogeneous masses with intense enhancement in the right frontal lobe, temporal lobe, corpus callosum, left cuneus, suprasellar region, and right cerebellum. Pathological examination showed a neoplastic lesion composed of plentiful epitheloid or spindle cells. The cell had pink cytoplasm of vacuolation and foam with deviated nucleus absent of atypia and mitosis. The histiocytic markers including CD163, CD11c, Mac387 and CD68 were positive, whereas S-100, CD1a, GFAP, CD21, CD23 and so on were negative immunohistochemically. CONCLUSIONS: Intracranial XD without systemic involvement was extremely rare, which was supposed to be considered in differential diagnosis with other neoplasms of histiocytic origin or gliomas.